RANCANG BANGUN SISTEM ADMINISTRASI DI SMKS 1 PEMBANGUNAN KOTA BENGKULU MENGGUNAKAN ARSITEKTUR TWO-TIER - Anisa Kurnia Putri; Sapri Sapri; Deri Lianda (Smart Education, 2024)
Abstract: SMKS 1 Pembangunan of Bengkulu City is one of the Private Vocational High Schools in Bengkulu City, Bengkulu Province. In the process of managing student administrative data at school, especially the administration of tuition payments, it uses an office application package, namely Microsoft Excel. The administration system at SMKS 1 Pembangunan Bengkulu City using Two Tier Architecture can simplify the process of managing administrative data at school, especially the payment of tuition fees and student development fees, can provide information on which students have not paid tuition fees and student development fees, and can facilitate the school in giving warnings to students in the form of letters to make payments. Two Tier architecture is built to allow the administration system at SMKS 1 Pembangunan to be accessed by more than 1 laptop/ client on the same network. Based on the tests that have been carried out, it is found that the administration system at SMKS 1 Pembangunan Bengkulu City using two tier architectures has run well and as expected and the application can facilitate the process of managing administrative data in schools, especially payment of tuition fees and student development fees. Keywords: administration system, smks 1 pembangunan bengkulu city, two-tier architecture Abstrak: SMKS 1 Pembangunan Kota Bengkulu merupakan salah satu Sekolah Menengah Kejuruan Swasta yang terdapat di Kota Bengkulu Provinsi Bengkulu. Dalam proses pengelolaan data administrasi siswa di sekolah khususnya administrasi pembayaran uang sekolah sudah menggunakan paket aplikasi office yaitu Microsoft Excel. Sistem administrasi di SMKS 1 Pembangunan Kota Bengkulu menggunakan Arsitektur Two Tier dapat mempermudah proses pengelolaan data administrasi di sekolah khususnya pembayaran uang SPP dan uang pembangunan siswa, dapat memberikan informasi siapa saja siswa yang belum membayar uang SPP dan uang pembangunan siswa, serta dapat mempermudah pihak sekolah dalam memberikan peringatan ke siswa berupa surat untuk melakukan pembayaran. Arsitektur Two Tier dibangun guna memungkinkan sistem administrasi di SMKS 1 Pembangunan dapat diakses lebih dari 1 laptop/client yang berada pada jaringan yang sama. Berdasarkan pengujian yang telah dilakukan didapatkan hasil bahwa sistem administrasi di SMKS 1 Pembangunan Kota Bengkulu menggunakan arsitektur two tier sudah berjalan dengan baik dan sesuai dengan harapan dan aplikasi dapat mempermudah proses pengelolaan data administrasi di sekolah khususnya pembayaran uang SPP dan uang pembangunan siswa Kata kunci: sistem administrasi, smks 1 pembangunan kota bengkulu, arsitektur two-tier